Research capacity and initial teacher education reform: Irish experiences, international perspectives - Gleeson, Jim; Sugrue, Ciaran; O'Flaherty, Joanne (Teaching and Teacher Education, 2017)
As globalisation intensifies and economies struggle to address ‘austerity’, educational reform continues unabated. In the case of initial teacher education (ITE) the pendulum swings between practice and research with a growing emphasis on teacher educators' expertise. International ITE discourses provide an important context for recent Irish policy and reforms. Against this backdrop, the findings of a systematic study of the research capabilities and activities of ITE faculty are critically analysed and discussed. The evidence indicates a considerable mismatch between policy intentions and teacher educators' current capacities. Policy implications are identified and discussed and their possible significance for other systems considered.